Transição de cuidados de enfermagem: ISBAR na promoção da segurança dos doentes – revisão scoping - Esteves Figueiredo, Ana Rita; Ferreira dos Santos Potra, Teresa Maria; Bernardes Lucas, Pedro Ricardo (Ámbitos. Revista Internacional de Comunicación, 2020)
The issue of patient safety during transfers has been gaining increasing importance at national and international levels, particularly with the proliferation of literature on the need for improvements in the health care transition. The scientific evidence shows that effective communication among health professionals increases patient safety. Effective communication can be achieved through the use of structured tools that guide the transfer of information, such as ISBAR technique (Identification, Current Situation, Background, Assessement, Recommendations), which is often recommended for the information transmission process’. Our objective is map out and analyse the scientific evidence related to the advantages of using the ISBAR technique in the transitions, by nurses, in hospital settings. It was conducted a three-step search strategy according to the Joanna Briggs Institute (2015). 1) A search of MEDLINE and CINAHL was undertaken, followed by an analysis of the words contained in the title, abstract and the index terms; 2) The keywords and index terms were searched across all the included databases; 3) Search of the reference lists of all the included articles. Results show that ISBAR improves the transfer of information and safeguards patient safety, as well as the handover information. The transfer is performed efficiently and timely. Professionals’ hierarchy is leveled and assumptions are minimized. Concluding the use of ISBAR has improved the handover about patient’s reasons for transfer and condition, promoting simplicity, clarity and safety during clinical transfers.